Transitioning of IT Companies from Waterfall to Agile Methodologies - Zhbajnova Mircheska, Aleksandra; Antovski, LJupcho (My University, 2020)
Flexibility and quick response to demands are imperative in today’s business environment, as the rapid pace of technology, innovation and develop- ment requires organizations to deliver results faster than ever. The traditional development methodologies, like waterfall, cannot respond to the rapid increase of the business needs. Numerous organizations are starting to move towards new agile methodologies. Overspend budgets, missed deadlines, solutions that did not met the business requirements, are some of the main reasons that forced organizations to transition to agile. The goal of this paper is to elaborate the transition phases of the organization from waterfall to agile methodologies. We have presented the characteristics of an agile/digital organization and introduced the microservices architecture as phase in the agile progression. Finally, we showcase the results of the analysis of the current IT architecture in Makedonski Telekom and how it fits in the new digital world, as well as the process of creation of the transition roadmap in Makedonski Telekom towards creating the new IT microservices based architecture.
Keywords: Agile, Digital organization, Agile transformation